Assessing knowledge, attitudes, and practices regarding Mpox among healthcare workers at a rural teaching hospital in Bihar - Singh, Tulika; Sharma, Sanju (International Journal Of Community Medicine And Public Health, 2025)
Background: Mpox is a viral zoonotic disease that has garnered global attention due to recent outbreaks. Healthcare workers (HCWs) play a critical role in managing such infectious diseases, making their knowledge, attitudes, and practices (KAP) essential for effective disease control. This study aimed to assess the KAP regarding Mpox among healthcare workers at a rural teaching hospital in Bihar, India. Methods: A cross-sectional survey was conducted among 120 healthcare workers, including interns, residents, faculty, and nursing staff. A structured, self-administered questionnaire was used to assess knowledge, attitudes, and practices related to Mpox. Data were analyzed using descriptive statistics, chi-square tests, and logistic regression. Results: A majority of participants (65.8%) had poor knowledge about Mpox, with younger healthcare workers (<35 years) showing better understanding. Most participants recognized Mpox as a public health threat but lacked confidence in managing cases. Compliance with infection control practices was high, but only 56.7% had received specific infectious disease training. Conclusions: Significant knowledge gaps exist among healthcare workers regarding Mpox, highlighting the need for targeted training and awareness programs to improve preparedness and response to Mpox and other emerging infectious diseases in rural healthcare settings.